Kesiapan Unit Rekam Medis Klinik dalam Menghadapi Akreditasi - Karina Amalia Sholihah (Universitas Airlangga, 2018)
Background: First Level Clinic is a health facility that provides first-layer clinical services to the community. Efforts that can be made to improve the quality and safety of clinical services at the Pratama clinic are through accreditation. The medical record unit is part of the Pratama clinic support service unit included in the Pratama clinical accreditation assessment section. The readiness of medical record units needs to be assessed to see what documents and implementations do not yet exist and are done. Identification of readiness of Clinic X medicalrecord unit accreditation was carried out two years earlier in 2015.Aims: The purpose of this study was to determine the continuity of readiness of medical record unit accreditationin 2018.Method: This study was an observational descriptive study using a cross-sectional design. Data collection was carried out through observation and interviews with medical record officers., Analysis was done by comparing the prediction of Clinic X medical record unit accreditation readiness scores between 2015 and 2018.Results: The result showed that the prediction score increased from 41.7% in 2015 to 65.8% in 2018. The comparison of readiness for accreditation can be used as an evaluation to complement the needs of documents that do not yet exist and procedures that have not been implemented.Conclusion: The clinic has not been accredited because most of the elements being evaluated were the incomplete supporting documents. The clinic can make a framework, determine the method, and analyze the instruments based on the suitable method.Keywords: accreditation, medical record, primary clinic